IMPROVING MATHEMATICS LEARNING ACTIVITIES USING COOPERATIVE TYPE LEARNING OF STUDENT TEAMS ACHIEVEMENT DIVISION - Rahmawati Rahmawati; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2019)
The teacher learning-centered causes the students to be less active in responding to the explanation due to students' different understanding levels. Therefore, it is necessary to improve the students learning activities. This study aims to enhance student learning activities in learning mathematics by using Student Teams Achievement Division (STAD) learning model. This study is a classroom action research consisting of two cycles. This research is the students of class VII C Junior High School (SMP) Muhammadiyah 9 Yogyakarta academic year 2017/2018. The object of this research is the improvement of student learning activity in learning mathematics. The data collection techniques organized as observation, interview, and success criteria of this study are marked by increasing the average percentage of student learning activities by at least 61%. It is called a good category. The results show that the learning model with STAD can improve students' learning activities in learning mathematics Class VII C. it can be seen from the average percentage of the student learning activities' observations in cycle I from 54.91% criteria. It gains in cycle II about 67.73% with good criteria. Moreover, students' interviews show an improvement in students' learning activities from cycle 1 to cycle II.